Improving students’ interest in music subject through practical learning in junior high school - Dani Nur Saputra; Dian Herdiati (Fakultas Sastra Universitas Negeri Malang, 2021)
Improving students’ interest in music subject through practical learning in junior high schoolThis research aims to investigate problems and ways to increase students’ interest in music learning with practical learning methods. This study uses descriptive qualitative and quantitative (mixed) methods. Data were collected by means of questionnaires, observations and interviews. They were then analyzed by calculating the presentation of the success of the actions in this study. Indicator analysis consists of several aspects, including affective data (attitudes) obtained from observations, cognitive (knowledge) obtained from the students’ assessment, and the questionnaire analysis of the research sample. Researchers took a research sample at one of the schools in Jakarta. Then the researchers randomly selected 15 students from different classes in the school as research participants. The results showed that practical learning could increase students’ interest by 87% in category A with a very satisfying indexation when compared to the previous method applied by most teachers, the classical learning method.Keywords: practice learning, students’ interest, music learning, music educationMeningkatkan minat belajar musik siswa melalui pembelajaran praktek di SMPPenelitian ini bertujuan untuk mengkaji masalah dan berupaya untuk meningkatkan minat belajar musik siswa dengan metode pembelajaran praktek. Penelitian ini menggunakan metode deskriptif kualitatif dan kuantitatif (campuran). Pengumpulan data dilakukan dengan kuesioner, observasi, dan wawancara. Pengumpulan data tersebut kemudian dianalisis dengan menghitung penyajian keberhasilan tindakan dalam penelitian ini. Analisis indikator terdiri dari aspek data afektif (sikap) yang diperoleh dari observasi dan aspek kognitif (pengetahuan) yang diperoleh dari penilaian siswa, serta hasil analisis angket sampel penelitian. Peneliti mengambil sampel penelitian di salah satu sekolah di Jakarta. Kemudian peneliti memilih secara acak 15 siswa dari kelas yang berbeda di sekolah tersebut sebagai objek penelitian. Hasil penelitian menunjukkan bahwa pembelajaran praktik dapat meningkatkan minat siswa sebesar 87% pada kategori A dengan indeksasi yang sangat memuaskan dibandingkan metode sebelumnya yang diterapkan oleh sebagian besar guru, yaitu metode pembelajaran klasikal.Kata kunci: pembelajaran praktek, minat siswa, pembelajaran musik, pendidikan musik